ADAPTATION OF THE «5 CAPITAL» CONCEPT FOR THE ANALYSIS OF RESOURCE POTENTIAL AT THE COMMUNITY LEVEL - Malyshivskyi , T.V.; Stefinin , V.V. (The actual problems of regional economy development, 2022)
The aim of the article is to study the possibilities of creating a unified system of assessment of resource potential at the community level by analyzing existing methods of assessment and adaptation of foreign approaches to the assessment of resources at the local level. To this end, the article clarifies the theoretical essence of the concept of «resource potential of the territorial community» and identifies its components. Approximate components of the analytical part of strategic and forecast documents of amalgamated communities in different methodological documents are compared. The existing methods of developing socio-economic strategies at the local and regional levels are analyzed for the presence of practical recommendations for communities to assess resource potential; the necessity of developing a universal approach to assessing the resource potential of communities on the example of adapting the concept of Jonathan Porritt's «5 capitals» is substantiated. The research used methods of analysis, systematization, grouping, and abstraction. The information base of the research consisted of scientific works of domestic and foreign economists and legal documents on the development of strategies for socio-economic development at the local and regional levels. The scientific novelty of the obtained results is the adaptation of Jonathan Porritt's concept of «5 capitals» to the assessment of resource potential at the community level. In particular, the model framework we propose for use in assessing resource potential at the level of territorial communities will consist of 7 capitals (types of resources): Natural; Human; Social; Industrial; Financial; Institutional capacity of local governments; Infrastructure component. The results of the study can be used by local authorities in developing strategic and forecasting documents for local communities. We believe that the use of a unified scientific model of resource capital assessment by communities will increase the effectiveness of the assessment, allow communities to compare indicators both over time and between different communities, and promote community cooperation and more intensive capital movements between them.